Rotaviruses and Rotavirus Vaccines - Bines, Julie; Donato, Celeste (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This special edition of Pathogens brings together a breadth of information on rotavirus and global rotavirus vaccines, to highlight rotavirus research from across the world that represents recent advances in our knowledge of vaccine effectiveness, rotavirus epidemiology, genotypic diversity, and genomic characterisation.